Analisis Fiqih Bi’ah Atas Pencabutan Izin Usaha Pertambangan di Kawasan Raja Ampat - Amirullah, Muhammad Azrul; Hilman, M. Akbar; Akbar, Nouma Zidan; Anis, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Ecological jurisprudence, as a branch of science that studies the relationship between Islamic law and the environment, highlights the importance of maintaining the balance of nature and environmental sustainability. This article examines the revocation of mining permits in the Raja Ampat region through the perspective of ecological jurisprudence, as part of a religious response to contemporary environmental issues. Raja Ampat, known as an area with the highest marine biodiversity in the world, faces serious threats from mining activities, particularly nickel. Through a qualitative-descriptive approach and normative analysis of fiqh principles such as maslahat (benefit), the prohibition of damage (prohibition of facades on the earth), and the responsibility of humankind as a vicegerent (khalifah) towards nature, this article highlights how Islamic values can serve as an ethical and spiritual basis for preserving the environment. The government's revocation of mining permits is seen as aligned with the principles of ecological jurisprudence, which emphasize ecological justice and the protection of living creatures. This study recommends the integration of religious values into environmental policies as an effort to realize equitable sustainable development.